Novel absorption refrigeration system with a hollow fiber membrane-based generator. (July 2016) - Hong, Sung Joo; Hihara, Eiji; Dang, Chaobin
Highlights: Propose the hollow fiber membrane-based generator as an automobile application. Conduct the parametric steady-state simulation on the novel LiBr–water single effect absorption cooling cycle combined with the hollow fiber membrane-based generator. Analyze the heat and mass transfer in the proposed membrane-based generator. Investigate the cooling capacity and COP under various operating conditions. Compare the proposed absorption cycle with the conventional cycles. Abstract: Vapor absorption refrigeration systems using the LiBr–water pair can be an alternative to existing automobile air-conditioning systems. To this purpose, the new system must be compact enough to fit into automobiles, and robust against sloping roads and unexpected vibrations while driving. The system uses a micro-porous hydrophobic hollow fiber membrane-based generator (HFM-G) instead of the conventional generator in the absorption cycle. HFM-G extracts water vapor from the LiBr solution that is mechanically constrained by a hydrophobic membrane. This paper presents the results of a parametric steady-state simulation investigating how the HFM-G affects the proposed absorption cooling cycle. We first describe the mechanism of the HFM-G, and the system performance of the proposed cycle under various operating conditions is examined. Simulation results show that the proposed system can achieve a cooling capacity and COP of approximately 2.88 kW and 0.63, respectively, by incorporating the solution recirculation process.